Queens, consorts, concubines : Gregory of Tours and women of the Merovingian elite - Dailey, E. T. (Mnemosyne, Supplements, 2015)
Gregory of Tours hoped to inspire the believers in sixth-century Gaul with examples of righteous and wicked deeds and their consequences. Critiquing his own society, Gregory contrasted vengeful queens, rebellious nuns, and conniving witches with pious widows, humble abbesses, and tearful saints. By examining his thematic treatment of topics including widowhood, marriage, sanctity, authority, and political agency, Queens, Consorts, Concubines reassesses the material shaped by such concerns, including e.g. Gregory's accounts of Brunhild, Fredegund, Radegund, and other important elite women, Merovingian political policies (marital alliances, ecclesiastical intrigue, even assassinations), and seemingly unrelated topics such as Hermenegild's rebellion and the career of Empress Sophia. The result: a new interpretation of an important witness to the transformations of Late Antiquity.